2002
DOI: 10.1243/030932402320950161
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the fatigue and fretting performance of a representative aero-engine spline coupling

Abstract: The fatigue behaviour of a representative high-performance aero-engine spline coupling is investigated under test conditions designed to simulate in-service conditions. The test load cycles consist of major cycle torque and axial load, simulating maximum thrust, combined with minor cycle rotating bending moment and fluctuating torque, simulating life-limiting conditions at take-off. The objective of the study is to develop understanding of the fatigue behaviour of the coupling over a range of loading condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 19 publications
0
57
0
Order By: Relevance
“…The cylindrical specimens are also 44 mm long with the diameter of the half-cylindrical specimen being 12 mm. The substrate materials used in the current study are a high strength steel (SCMV) and a titanium alloy (Ti-6Al-4V), focussed on aeroengine applications where a number of components potentially experience fretting problems such as in the spline coupling [12] and the dovetail fan blade joint [13,14]. Untreated specimen blanks were manufactured from SCMV and Ti-6Al-4V.…”
Section: Materials and Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The cylindrical specimens are also 44 mm long with the diameter of the half-cylindrical specimen being 12 mm. The substrate materials used in the current study are a high strength steel (SCMV) and a titanium alloy (Ti-6Al-4V), focussed on aeroengine applications where a number of components potentially experience fretting problems such as in the spline coupling [12] and the dovetail fan blade joint [13,14]. Untreated specimen blanks were manufactured from SCMV and Ti-6Al-4V.…”
Section: Materials and Specimensmentioning
confidence: 99%
“…Finally, of course, a key benefit of an FE-based wear model is the possibility to investigate, at least computationally, the performance of coatings in complex geometry applications, e.g. real three-dimensional applications such as dovetail joints [14] and spline couplings [12].…”
Section: Coating Life Predictionmentioning
confidence: 99%
“…McFarlane et al [5], initially applied boundary element analyses to a helical splined coupling and validated the predictions against strain gauge and photo-elastic results. Leen et al [6][7][8][9] extended the approach to elastic plastic analyses using three-dimensional finite element (FE) models. Amongst other modes of potential failure, spline couplings subjected to cyclic loading are susceptible to plain fatigue, fretting fatigue and fretting wear.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst other modes of potential failure, spline couplings subjected to cyclic loading are susceptible to plain fatigue, fretting fatigue and fretting wear. The plain fatigue behaviour of spline couplings has been the subject of a number of studies [8][9][10][11][12], with three prominent sources of stress concentration identified; spline root/fillet torsional stresses, spline fillet bending stresses and friction enhanced contact stresses [8]. To improve the fatigue performance, spline profile (tooth thickness) modification by axial barrelling/crowning has been employed in order to reduce the end-of-engagement contact stresses [6,7]; however, this further increases the complexity of analysis due to the dependence of the spline tooth contact area on torque level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation